New species, locality records and calling songs of crickets of the subfamily Phaloriinae (Orthoptera: Grylloidea: Phalangopsidae) from Malaysia - Tan, Ming Kai; Muhammad, Amira Aqilah; Abdullah, Nurul Ashikin; Japir, Razy; Chung, Arthur Y.c.; Robillard, Tony (Zootaxa, 2024)
Specimens representing three genera of Phaloriinae—Borneloria Gorochov, 2018, Phaloria (Papuloria) Gorochov, 1996 and Trellius (Zatrellius) Gorochov, 1999—were collected from Peninsular and East Malaysia and examined here. We report a new locality record for Borneloria moorei (Chopard, 1940) in Johor, Peninsular Malaysia, the first record of this genus in Malay Peninsula. From Sandakan, East Malaysia, we discovered a new species of Trellius (Zatrellius) and describe here: Trellius (Zatrellius) puntung sp. nov. We also recorded the previously unknown calling songs of Phaloria (Papuloria) tristis Gorochov, 2014 and Trellius (Zatrellius) puntung sp. nov. and describe them here.